MO644: Comparative Analysis of Survival and Morbidity in Home and Hospital Haemodialysis. (3rd May 2022) - Todorov Sakic, Verica; Djuric, Petar; Jankovic, Aleksandar; Bulatovic, Ana; Bjedov, Jelena; Djuric, Zivka; Pešić, Snezana; Dimkovic, Nada; Naumovic, Radomir
Abstract: BACKGROUND AND AIMS: Many studies have shown that home haemodialysis (HOHD) provides fewer complications and better outcomes as compared with hospital haemodialysis (HHD). The aim of this study was to compare morbidity and survival in patients on HOHD and HHD. METHOD: We analysed 26 prevalent HOHD patients who were matched with 52 HHD patients according to sex, age and Davies Comorbidity Index (DCI). DCI is based on seven groups of comorbidities: ischaemic heart disease (IHD), left ventricular dysfunction (LVD), peripheral vascular disease (PVD), malignancy, diabetes mellitus (DM), systemic collagen vascular disease and other significant pathology. Grade 0 had patients without any of these comorbidities, grade 1 those with 1–2 and those with 3 or more comorbidities had grade 2. Patients were followed from January 2011 to January 2020. We analysed an overall number of hospitalizations during the study period, a number of hospitalizations per year (annual hospital admission rate) and longevity of in-hospital stay (days). We categorized each hospitalization into 1 of 4 causes: cardiovascular disease (CVD), infection, vascular access dysfunction, or other cause. RESULTS: Median age for HOHD and HHD patients was 55.7 and 56 years respectively and 77% of patients in both groups were men. Majority of the patients in both groups had DCI 1 (65%), 31% had DCI 0 and only 4% had DCI 2. The most common comorbidity for both HOHD and HHD patients was IHD (35% and 29% respectively), followed by HCV infection (35% and 17% respectively) and PVD (11.5% and 15% respectively). There was no difference between HOHD and HHD patients in an overall number of hospitalization (3.7 ± 3.3 versus 3.9 ± 2.8; P = .47), nor in annual admission rate for all-cause morbidity (0.5 ± 0.4 versus 0.6 ± 0.4; P = .28), but HHD patients had longer in-hospital stay (7.4 ± 9.8 days versus 9.3 ± 8.7 days; P = .05). Cause-specific morbidity showed that HHD patients had a more frequent annual admission rate for CVD (0.2 ± 0.1 versus 0.4 ± 0.3; P = .05), while there were no differences for infections (0.3 ± 0.2 versus 0.3 ± 0.3; P = .9) nor vascular access complications (0.3 ± 0.3 versus 0.4 ± 0.3; P = .3). Also, annual in-hospital stays for CVD (3.0 ± 3.1 versus 4.0 ± 4.5 days; P = .5), infection (6.4 ± 7.5 versus 5.7 ± 7.6 days; P = .6) and vascular access complications (6.0 ± 7.0 versus 7.7 ± 7.8 days; P = .5) did not differ between HOHD and HHD group. Kaplan–Meier curve revealed that survival in HOHD and HHD patients were 92.3% versus 90.4% at 3 years, 84.6% versus 70.2% at 5 years and 55.7% versus 50% at 9 years (log-rank test P = .5). CONCLUSION: Our study has shown that HOHD and HHD patients had similar hospitalization rates, but patients on HOHD had better rehabilitation and shorter hospitalizations for all-cause morbidity. Despite this, HHD and HOHD patients had similar survival rates.